THE EFFORT OF TB CADRE IN THE IMPROVING OF THE SUCCESS OF TB THERAPY AND REDUCING SIDE EFFECTS OF ANTI TUBERCULOSIS DRUGS - Dewi Rokhmah; Khoiron Khoiron; Elly Nurus Shakinah; Ema Rahmawati (UNEJ e-Proceeding, 2016)
Sumberjambe District is one of districts in Jember Regency, which become case-finding pouches for tuberculosis (TB). In order to tackle TB, Sumberjambe District has a community which called “Sayang TB Community”. The existence of community is able to increase the number of CDR of 28% in 2003 to 80% in 2011. In addition, cure rate is one indicator of the success of TB. To obtain healing, TB patients should consume Anti Tuberculosis Drugs (ATD) for 6 months. The side effects appear 2 weeks to 2 months after use of OAT, one of which is hepatotoxic. TB patients with hepatotoxicity requires a longer healing time. Supplementation herbal medicine made from turmeric, ginger and meniran in patients with TB is able to tackle hepatotoxic and speed healing. This research is a quantitative study with an experimental approach to determine the increase of knowledge TB cadre and patients who become members of “Sayang TB Community” by pre-test and post-test. The knowledge about the disease tuberculosis and processing skills to make herbal medicine made from turmeric, ginger and meniran as a food supplement in the treatment of TB. The results showed that there is an increased knowledge of participants, while the decline in the percentage of correct answers on the results of pre-test and post-test showed that the knowledge of trainees is still lacking. In addition there is a material that is difficult to understand by the participants.